2019
DOI: 10.1136/archdischild-2018-316693
|View full text |Cite
|
Sign up to set email alerts
|

Origins of disparities in preventable child mortality in England and Sweden: a birth cohort study

Abstract: ObjectiveTo compare mortality in children aged <5 years from two causes amenable to healthcare prevention in England and Sweden: respiratory tract infection (RTI) and sudden unexpected death in infancy (SUDI).DesignBirth cohort study using linked administrative health databases from England and Sweden.Setting and participantsSingleton live births between 2003 and 2012 in England and Sweden, followed up from age 31 days until the fifth birthday, death or 31 December 2013.Main outcome measuresThe main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
0
12
0
2
Order By: Relevance
“…Similar to our findings, Tambe et al 10 11 found higher CYP mortality rates for infections in the UK compared with Sweden and others have shown poor UK outcomes and slow rates of decline for childhood infections such as pneumonia and meningococcal disease. [12][13][14][15] We found the UK to have significantly higher mortality for common infections than the EU15+ in children aged 1-9 years old (both sexes), boys aged 10-14 and girls aged [15][16][17][18][19], and ranked in the bottom three countries across all age groups and both sexes. Although common infections account for a relatively small proportion of total CYP deaths, reducing UK mortality to the EU15+ median would save around 85 lives a year in those aged 1-19 years old (see online supplementary material).…”
Section: Comparison With the Literaturementioning
confidence: 71%
See 4 more Smart Citations
“…Similar to our findings, Tambe et al 10 11 found higher CYP mortality rates for infections in the UK compared with Sweden and others have shown poor UK outcomes and slow rates of decline for childhood infections such as pneumonia and meningococcal disease. [12][13][14][15] We found the UK to have significantly higher mortality for common infections than the EU15+ in children aged 1-9 years old (both sexes), boys aged 10-14 and girls aged [15][16][17][18][19], and ranked in the bottom three countries across all age groups and both sexes. Although common infections account for a relatively small proportion of total CYP deaths, reducing UK mortality to the EU15+ median would save around 85 lives a year in those aged 1-19 years old (see online supplementary material).…”
Section: Comparison With the Literaturementioning
confidence: 71%
“…The 3-year lagged mean number of deaths in CYP aged [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in 2015 in the UK was 2110 (1281 boys and 829 girls), and the 3-year lagged all-cause mortality rate was 14.6 per 100 000. Of the deaths, 44.8% were among 15-19 year olds, 15.7% were among 10-14 year olds, 14.6% were among 5-9 year olds and 24.9% were among 1-4 year olds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations